Answers

2014-11-29T16:43:26+08:00

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Product of binomial:
(x+2)(x+3)
You can write it as:
x(x+3)+2(x+3)
Distribute
x²+3x+2x+6
=x²+5x+6

Now, the product of trinomial:
(x²+x-2)(x²+2x+1)
You can write it as:
x²(x²+2x+1)+x(x²+2x+1)-2(x²+2x+1)
=x^{4}+2x^{3}+x^{2}+x^{3}+2x^{2}+x-2x^{2}-4x-2
=x^{4}+3x^{3}+x^{2}-3x-2

Hope this helps =)
0
2014-11-29T17:59:21+08:00
Multiplication of Binomial to Trinomial
( x+3)(x^2+2x+4) = n
   To solve n, do the distributive method.
x(x^2+2x+4) 3(x^2+2x+4)=x^3+2x^2+4x+3x^2+6x+12=x^3+5x^2+10x+12
0